Upfront FOLFOXIRI plus bevacizumab with or without atezolizumab in the treatment of patients with metastatic colorectal cancer (AtezoTRIBE): a multicentre, open-label, randomised, controlled, phase 2 trial. Issue 7 (July 2022) - Antoniotti, Carlotta; Rossini, Daniele; Pietrantonio, Filippo; Catteau, Aurélie; Salvatore, Lisa; Lonardi, Sara; Boquet, Isabelle; Tamberi, Stefano; Marmorino, Federica; Moretto, Roberto; Ambrosini, Margherita; Tamburini, Emiliano; et al.
Summary: Background: Immune checkpoint inhibitors have not shown clinical benefit to patients with metastatic colorectal cancer who had proficient mismatch repair (pMMR) or microsatellite stable (MSS) tumours in previous studies. Both an active combination chemotherapy (FOLFOXIRI; fluorouracil, leucovorin, oxaliplatin, and irinotecan) and bevacizumab seem able to increase the immunogenicity of pMMR or MSS tumours. We aimed to provide preliminary evidence of benefit from the addition of the anti-PD-L1 agent atezolizumab to first-line FOLFOXIRI plus bevacizumab in patients with metastatic colorectal cancer. Methods: AtezoTRIBE was a multicentre, open-label, randomised, controlled, phase 2 study of patients (aged 18–70 years with an Eastern Cooperative Oncology Group [ECOG] performance status of 0–2 and aged 71–75 years with an ECOG performance status of 0) with histologically confirmed, unresectable, previously untreated metastatic colorectal cancer and adequate organ function, who were recruited from 22 oncology centres in Italy. Patients were stratified according to centre, ECOG performance status, primary tumour site, and previous adjuvant therapy. A randomisation system incorporating a minimisation algorithm randomly assigned (1:2) patients via a masked web-based allocation procedure to two groups: the control group received first-line FOLFOXIRI (intravenous 165 mg/m 2 irinotecan, 85 mg/m 2 oxaliplatin, 200 mg/m 2 leucovorin, and 3200 mg/m 2 fluorouracil as a 48 h infusion) plus bevacizumab (5 mg/kg intravenously), and the atezolizumab group received the same regimen plus atezolizumab (840 mg intravenously). Combination treatments were administered up to eight 14-day cycles followed by maintenance with fluorouracil and leucovorin plus bevacizumab with or without atezolizumab, according to randomisation group, until disease progression, unacceptable adverse events, or consent withdrawal. The primary endpoint was progression-free survival, analysed by the intention-to-treat principle. Safety was assessed in patients who received at least one dose of the study treatment. The study recruitment is completed. The trial is registered with Clinicaltrials.gov, NCT03721653 . Findings: Between Nov 30, 2018, and Feb 26, 2020, 218 patients were randomly assigned and received treatment (73 in the control group and 145 in the atezolizumab group). At the data cutoff (Aug 1, 2021), median follow-up was 19·9 months (IQR 17·3–23·9). Median progression-free survival was 13·1 months (80% CI 12·5–13·8) in the atezolizumab group and 11·5 months (10·0–12·6) in the control group (hazard ratio [HR] 0·69 [80% CI 0·56–0·85]; p=0·012; adjusted HR 0·70 [80% CI 0·57–0·87]; log-rank test p=0·018). The most frequent all-cause grade 3–4 adverse events were neutropenia (59 [42%] of 142 patients in the atezolizumab group vs 26 [36%] of 72 patients in the control group), diarrhoea (21 [15%] vs nine [13%]), and febrile neutropenia (14 [10%] vs seven [10%]). Serious adverse events were reported in 39 (27%) patients in the atezolizumab group and in 19 (26%) patients in the control group. Two (1%) treatment-related deaths (due to acute myocardial infarction and bronchopulmonary haemorrhage) were reported in the atezolizumab group; none were reported in the control group. Interpretation: The addition of atezolizumab to first-line FOLFOXIRI plus bevacizumab is safe and improved progression-free survival in patients with previously untreated metastatic colorectal cancer. Funding: GONO Foundation, ARCO Foundation, F Hoffmann-La Roche, and Roche.